2014
DOI: 10.1002/art.38351
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Neuro‐Behçet's Disease

Abstract: Objective. To report the long-term outcome of neurologic involvement in patients with Behçet's disease (BD).Methods. We performed a retrospective analysis of 115 patients who fulfilled the international criteria for BD (57% male; median age 37 years [interquartile range (IQR) 30-46 years]) and had neuro-BD (NBD) after exclusion of cerebral venous thrombosis. Factors associated with relapse of NBD, inability to perform activities of daily living, and mortality were assessed.Results. Seventy-eight patients (68%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 38 publications
3
64
0
3
Order By: Relevance
“…[13][14][15][16] Results of these studies partially support our findings, but they have not examined whether patients smoke or not. Bilgin et al 2 have also reported that cystoid macular edema among current smoking patients with BD was significantly higher than nonsmoking patients, but smoking was inefficient on other ocular involvement.…”
Section: Discussionsupporting
confidence: 59%
“…[13][14][15][16] Results of these studies partially support our findings, but they have not examined whether patients smoke or not. Bilgin et al 2 have also reported that cystoid macular edema among current smoking patients with BD was significantly higher than nonsmoking patients, but smoking was inefficient on other ocular involvement.…”
Section: Discussionsupporting
confidence: 59%
“…Corticosteroid sparing was defined as a significant decrease of corticosteroid daily dose between the day of anti-TNF introduction and after 6 and 12 months of treatment. Relapses were defined as an occurrence of new BD manifestations and/or worsening of a preexisting manifestation requiring treatment intensification or modification [15,20,26]. Safety was assessed by the occurrence of side effects.…”
Section: Secondary End Pointsmentioning
confidence: 99%
“…We have previously revealed that the positive rate of HLA-B51 was nearly 90% in CPNBD [10,21]. Consistently, it has been shown that a positive HLA-B51 status was associated with a worse prognosis [20]. More importantly, no patients were given methotrexate, whereas all the patients were given corticosteroid and approximately 80% of the patients were given cyclophosphamide or azathioprine in the study [20].…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies have confirmed the poor long-term outcome of NBD [20]. It appears that the poor outcome might be a result of the presence of patients with CPNBD.…”
Section: Discussionmentioning
confidence: 88%